2007
DOI: 10.1111/j.1472-765x.2007.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteases from Bacillus: a new insight into the mechanism of action for rhizobacterial suppression of nematode populations

Abstract: Aims:  The aim of this study was to investigate the role of proteases in Bacillus spp. of rhizobacteria in suppressing nematode populations and to understand their mechanism of action. Methods and Results:  Rhizobacteria with nematicidal activity were isolated from soil samples of five root knot nematode‐infested farms. Among these strains, nematotoxicities of Bacillus strains were intensively analysed. Further assays of nematicidal toxins from Bacillus sp. strain RH219 indicated an extracellular cuticle‐degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 29 publications
1
55
0
5
Order By: Relevance
“…The described characterization and identification of this new P. veronii isolate, and the functional assignments of these candidate proteins have been reinforced. The cuticle of nematodes is rigid and is composed of proteins and lipids that can be affected by hydrolytic enzymes from nematicidal bacteria (Lian et al, 2007). Our results suggested that at least these hydrolytic enzymes might be involved in the nematicidal activity via cuticle degradation of connective tissues in their digestive tracts (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…The described characterization and identification of this new P. veronii isolate, and the functional assignments of these candidate proteins have been reinforced. The cuticle of nematodes is rigid and is composed of proteins and lipids that can be affected by hydrolytic enzymes from nematicidal bacteria (Lian et al, 2007). Our results suggested that at least these hydrolytic enzymes might be involved in the nematicidal activity via cuticle degradation of connective tissues in their digestive tracts (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License Lian et al, 2007). Recent surveys report that the bacteria Pseudomonas synxantha, Pseudomonas fluorescens, Bacillus subtilis, and Stenotrophomonas maltophilia showed toxic effect on eggs and juveniles under laboratory conditions indicating the occurrence of the production of antimicrobial metabolites (Ludwig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of resistant spores is a desirable feature for a biocontrol agent, since it provides greater field survival and longer shelf life to products formulated therefrom. In addition, Bacillus-based products are more environmentally safe than chemicals, and are compatible with conventional farming practices (Chen & Dickinson, 2004 (Kavitha et al, 2007;Lian et al, 2007;Tian et al, 2007;Mohammed et al, 2008;Araújo & Marchesi, 2009;Ann, 2013). The mechanisms of action of these bacteria against nematodes involve the production of nematotoxic substances, modification of root exudates of host plants, systemic resistance induction, and production of lethal proteases within the gut following the ingestion of the bacteria by the nematode (Araújo et al, 2002;Kavitha et al, 2007;Lian et al, 2007;Tian et al, 2007;Mohammed et al, 2008;Niu et al, 2010;Ann, 2013).…”
Section: Introductionmentioning
confidence: 99%